2017
DOI: 10.1091/mbc.e17-07-0459
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of amyloid precursor–like protein 1 trans interactions in cell–cell adhesion platforms investigated via fluorescence fluctuation spectroscopy

Abstract: The amyloid precursor–like protein 1 (APLP1) plays a role in synaptic adhesion and synaptogenesis. In this work, we use quantitative fluorescence microscopy to demonstrate the existence of APLP1–APLP1 trans interaction across cell–cell junctions and propose a model explaining the molecular mechanism driving APLP1 multimerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…In conclusion, the data currently available suggest that APLP2 dimerization is only moderately influenced by metal ion binding, whereas APP and APLP1 are affected more strongly. Moreover, APP trans-dimerization is modulated mainly by copper, whereas zinc affects predominantly APLP1 trans-dimerization (Baumkotter et al 2014;Mayer et al 2016;Dunsing et al 2017). Here, we demonstrate that copper promotes also APLP1 and APLP2 trans-dimerization and that zinc attenuates the trans-directed dimerization of APP, likely via a novel high-affinity zinc binding site in the E1 domain.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…In conclusion, the data currently available suggest that APLP2 dimerization is only moderately influenced by metal ion binding, whereas APP and APLP1 are affected more strongly. Moreover, APP trans-dimerization is modulated mainly by copper, whereas zinc affects predominantly APLP1 trans-dimerization (Baumkotter et al 2014;Mayer et al 2016;Dunsing et al 2017). Here, we demonstrate that copper promotes also APLP1 and APLP2 trans-dimerization and that zinc attenuates the trans-directed dimerization of APP, likely via a novel high-affinity zinc binding site in the E1 domain.…”
mentioning
confidence: 64%
“…6). Zincinduced trans-interaction of APLP1 has been reported before (Dunsing et al 2017), depending on a newly identified zinc binding site in the E2 domain of APLP1 (Mayer et al 2014(Mayer et al , 2016. It has been assumed that increased trans-interaction of APLP1 might be because of zinc-induced oligomerization of APLP1 within the plasma membrane, involving alterations in the submembraneous cytoskeleton.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations